Rural Land Use Disputes in Bahir Dar Zuria Woreda Community of Ethiopia - Asmare Shetahun Alemneh (Department of Agribusiness, Halu Oleo University Jointly with Perhimpunan Ekonomi Pertanian Indonesia - Indonesian Society of Agricultural Economics (PERHEPI/ISAE), 2024)
The objective of the paper is to assess rural land dispute in Bahir Dar Zuria Woreda of Wojer, Feresewoga, and Tentakerkose, Sebatamite, and Lejome kebeles. To achieve the objectives, the study has employed qualitative research approach with case study research design by using primary and secondary sources of data. Data were collected using focus group discussion, interviews, and non-participatory observation; and relevant literatures and documents are reviewed. Key informants and FGD participants were selected based on purposive and snowball sampling methods. The total number of informants participated in this study were 106. The data were analyzed qualitatively through the use of thematic analysis. It is found that rural land disputes were instigated due to various factors like the increases in population number, scarcity of farm land, poverty, the increase in rural land value, and weak rural land administration system, land registration and certification, increase in rural land value were the indirect causes of rural land disputes and the study identified the direct cause rural land disputes such as boundary disputes, inheritances disputes, transfer of land disputes, land dispute on access to road, drainage direction dispute, plant shade, land garbing, dispute on grazing land, divorce related disputes, compensation payment for expropriation of rural lands to the city, livestock destroy crops dispute, and ownership disputes. Rural land use dispute is better resolved through indigenous dispute resolution mechanisms. The government and other stockholders should give emphasis to the increasing land use dispute and needs to integrate the modern and indigenous conflict resolution mechanisms to mitigate the problem.